2017
DOI: 10.1097/rct.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diastolic Function in Hypertrophic Cardiomyopathy by Computed Tomography–Derived Analysis of Left Ventricular Filling

Abstract: This study suggests that simultaneous depiction of computed tomography-derived LV and LA volume changes can characterize diastolic dysfunction in HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“… 14 , 15 In the present study, we used cardiac computed tomography angiography (CTCA) to acquire complete and simultaneous LA and LV volumetric data to characterize the 3 components of LV diastolic filling. 16 We show that LA conduit function plays a key role in maintaining LV filling in advanced LVDD and strongly correlates with the development of pulmonary hypertension.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“… 14 , 15 In the present study, we used cardiac computed tomography angiography (CTCA) to acquire complete and simultaneous LA and LV volumetric data to characterize the 3 components of LV diastolic filling. 16 We show that LA conduit function plays a key role in maintaining LV filling in advanced LVDD and strongly correlates with the development of pulmonary hypertension.…”
mentioning
confidence: 67%
“… 19 , 20 LA expansion index, representing the relative LA volume changes during the reservoir phase, was calculated as follows: LA expansion indexI=(LAV max −LAV min )/LAV min . 15 , 16 , 18 , 21 23 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been already shown that cardiac CT (CCT) may provide varying parameters for the assessment of diastolic dyfunction. [ 3 , 87 , 88 ] Similar to echocardiography, CCT has been applied to measure early and late diastolic filling rates for the assessment of diastolic function. However, LV filling rates are not recommended as the only indices of diastolic function due to their dependence on LV relaxation and LV filling pressure.…”
Section: Cardiac Computed Tomography In Hfpefmentioning
confidence: 99%